Impact of Comorbidities on Tumor Necrosis Factor Inhibitor Therapy in Psoriatic Arthritis: A Population‐Based Cohort Study. Issue 4 (7th March 2018) - Ballegaard, Christine; Højgaard, Pil; Dreyer, Lene; Cordtz, René; Jørgensen, Tanja Schjødt; Skougaard, Marie; Tarp, Simon; Kristensen, Lars Erik
Abstract : Objective: The objective of this population‐based cohort study was to investigate the impact of comorbidities on disease activity, treatment response, and persistence with the first‐tried tumor necrosis factor inhibitor (TNFi) in patients with psoriatic arthritis (PsA). Methods: Data on patient characteristics, disease activity, and treatment response and persistence were obtained from the DANBIO registry. Information on comorbidities according to the Charlson Comorbidity Index (CCI) was obtained through linkage with the Danish National Patient Register. Kaplan‐Meier plots and Cox proportional hazard regression analyses were performed. Percentages of patients achieving relevant clinical responses were calculated. Results: We identified 1, 750 patients eligible for analyses. Patients with higher CCI scores had higher disease activity measures at baseline and increased occurrence of depression and/or anxiety. Kaplan‐Meier curves showed shorter persistence with treatment for patients with a CCI score ≥2 (log‐rank P < 0.001) and for patients with depression and/or anxiety ( P = 0.027) compared to patients without comorbidities. In multivariate analysis, a CCI score ≥2 was associated with reduced TNFi persistence compared with patients without comorbidities (hazard ratio 1.72 [95% confidence interval 1.26–2.37]; P = 0.001). A smaller proportion of patients with a CCI score ≥2 achieved European League Against Rheumatism (EULAR) good response ( P < 0.001) and EULAR good‐or‐moderate response ( P < 0.001) at 6 months compared with patients without comorbidities. Conclusion: The presence of comorbidities was associated with higher baseline disease activity, shorter TNFi persistence, and reduced clinical response rates in a cohort of Danish patients with PsA.